2014
DOI: 10.1002/jrs.4490
|View full text |Cite
|
Sign up to set email alerts
|

Raman analysis of multilayer automotive paints in forensic science: measurement variability and depth profile

Abstract: The aim of this work is to study the influence of several analytical parameters on the variability of Raman spectra of paint samples. In the present study, microtome thin section and direct (no preparation) analysis are considered as sample preparation. In order to evaluate their influence on the measures, an experimental design such as ‘fractional full factorial’ with seven factors (including the sampling process) is applied, for a total of 32 experiments representing 160 measures. Once the influence of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The analytical parameters influencing the variability of Raman spectra of car paint samples were studied by Lambert et al [46] Through 32 experiments and 160 measurements, including chemometrics, it was found that the only factor that significantly influences the Raman spectra variability is the sample preparation. No sample preparation gives less variability than the analysis on cross sections, even in the case of clearcoat presence.…”
Section: Forensic Applications In Art and Archaeology And Authenticitmentioning
confidence: 99%
“…The analytical parameters influencing the variability of Raman spectra of car paint samples were studied by Lambert et al [46] Through 32 experiments and 160 measurements, including chemometrics, it was found that the only factor that significantly influences the Raman spectra variability is the sample preparation. No sample preparation gives less variability than the analysis on cross sections, even in the case of clearcoat presence.…”
Section: Forensic Applications In Art and Archaeology And Authenticitmentioning
confidence: 99%
“…Grauw et al adapted this formalism and considered a Gaussian beam, instead of a spherical beam, for the image‐formation in the back‐focal plane, and accordingly obtained a Lorenzian profile of Raman intensity from a thin polystyrene film. For thick transparent samples, the effect of refractive index mismatch has been studied in several articles . Everall formulated the axial spreading of focus inside the sample between paraxial and oblique rays using a geometrical optic approach and provided an analysis of the Gaussian intensity distribution within the axially broadened depth‐of‐focus as a function of the starting position of the ray on the objective, that is, the pupil parameter.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the otherwise near-perfect converging beam is broadened in the axial direction inside the sample. This results in dramatic deterioration of the depth-of-focus and makes it difficult to accurately reconstruct the true depth profile and to extract effective parameters, especially axially inhomogeneous parameters such as thickness [7][8][9][10][11][12] and material properties. [13][14][15] This particular problem is prevalent in high numerical aperture (NA) dry objective systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forensic evidence involving automobiles frequently comes in the form of small paint chips and smears, which are valuable forms of trace contact evidence, obtained from vehicles involved in hit‐and‐run accidents, road accidents, or from victims of vehicular homicide. The chemical analysis of such trace evidence is used to link suspected vehicles with traces collected at an accident scene and for the potential discrimination of vehicles by their make, model, and year using reference samples. Examinations of the layer structure, color, and chemical composition of the paint are some of the features that are routinely investigated.…”
Section: Introductionmentioning
confidence: 99%